Os acessos fixos à internet no Brasil e suas tecnologias - Marcelo Paiva da Motta (Confins)
The objective of this paper is to analyze the spatial pattern of internet access in Brazil in its different technologies, opposing the idea of annihilation of space which is often associated to its use. We show, both in the access in general and in each of its several technologies, that the internet spatial distribution in the consumption dimension follow the existing economic geography and urban hierarchy. The application of a generalized additive model (GAM) correlating internet access levels with the local gross product supports this idea and also shows that there are specific areas in the country where the role of local institutions is important in increasing the amount of internet access, as in the state of Paraná.